2020
DOI: 10.24251/hicss.2020.138
|View full text |Cite
|
Sign up to set email alerts
|

Gameful Self-Regulation: A Study on How Gamified Self-Tracking Features Evoke Gameful Experiences

Abstract: Gamification has become one of the top engagement technology trends of recent times. It refers to designing and transforming systems, services, and activities to afford gameful experiences as good games do, commonly implemented through the utilization of familiar features from games. However, one of the persistent problems in academia and practice has been the lack of understanding of which systems features are more or less prone to facilitate which dimensions of the gameful experience. We investigate the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…It was followed by their feeling of guidance, more than half of the students reported that they had that feeling and, thirdly by sociability reporting that they had felt connected to other students and recognized for their achievements. These results are in line with state-of-the-art publications using the Gamefulquest questionnaire such as [47]. As a practical implication, it is important to keep the playfulness feeling of the SG supported by guidance and sociability as they seem to be key gameful dimensions to provide a positive gameful experience for High Schools learning programming.…”
Section: A Evaluation Of Results and Implicationssupporting
confidence: 85%
“…It was followed by their feeling of guidance, more than half of the students reported that they had that feeling and, thirdly by sociability reporting that they had felt connected to other students and recognized for their achievements. These results are in line with state-of-the-art publications using the Gamefulquest questionnaire such as [47]. As a practical implication, it is important to keep the playfulness feeling of the SG supported by guidance and sociability as they seem to be key gameful dimensions to provide a positive gameful experience for High Schools learning programming.…”
Section: A Evaluation Of Results and Implicationssupporting
confidence: 85%
“…If goals are contextually helpful, providing information concerning the "why" and "how" of changing nutrition behavior can lead to meaningful GE that enables long-term changes [38,39]. Goals being the most preferred GE go in line with the results found by Hassan et al [18], who state that goalsetting is the core of gamification design. Additionally, one might interpret that goals are already familiar to users in the context of nutrition, due to sayings like "5 fruits a day" and Schmidt-Kraepelin et al [50] state that prior knowledge of a GE in the given context might explain the higher preference.…”
Section: Discussionmentioning
confidence: 67%
“…Other successful digital health interventions have incorporated gamification features, promoting intrinsic and extrinsic motivators [59][60][61]. Similarities can also be recognized between these findings and wider work on persuasive systems design in relation to shaping health behaviors during the perioperative period [62][63][64][65][66]. Oinas-Kukkonen and Harjumaa [62] proposed that persuasion principles (including praise and rewards) should be considered as requirements in software design.…”
Section: Principal Findingsmentioning
confidence: 68%